2015
DOI: 10.1371/journal.pbio.1002269
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Dendritic Cell-Derived IL-12 by Endogenous Glucocorticoids Is Protective in LPS-Induced Sepsis

Abstract: Sepsis, an exaggerated systemic inflammatory response, remains a major medical challenge. Both hyperinflammation and immunosuppression are implicated as causes of morbidity and mortality. Dendritic cell (DC) loss has been observed in septic patients and in experimental sepsis models, but the role of DCs in sepsis, and the mechanisms and significance of DC loss, are poorly understood. Here, we report that mice with selective deletion of the glucocorticoid receptor (GR) in DCs (GRCD11c-cre) were highly susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 50 publications
0
66
0
Order By: Relevance
“…Moreover, the physiological effects of glucocorticoids on dendritic cells, regulatory T cells, or Th17 cells in the endometrium have not been studied. Dendritic cell-specific NR3C1 knockout mice have been utilized in models of sepsis and arthritis but have not been evaluated for functions relating to fertility [95, 96]. T cell-specific ablation of NR3C1 has been reported, although Cre recombinase activity occurs early in T-cell development and prevents discriminating the contribution of glucocorticoid signaling among T cell subtypes [91].…”
Section: Reproductive Immunology: Immuno-modulatory Actions Of Glucocmentioning
confidence: 99%
“…Moreover, the physiological effects of glucocorticoids on dendritic cells, regulatory T cells, or Th17 cells in the endometrium have not been studied. Dendritic cell-specific NR3C1 knockout mice have been utilized in models of sepsis and arthritis but have not been evaluated for functions relating to fertility [95, 96]. T cell-specific ablation of NR3C1 has been reported, although Cre recombinase activity occurs early in T-cell development and prevents discriminating the contribution of glucocorticoid signaling among T cell subtypes [91].…”
Section: Reproductive Immunology: Immuno-modulatory Actions Of Glucocmentioning
confidence: 99%
“…These changes in DC markers are likely to represent an altered function of DCs in the setting of inflammatory conditions [64]. In a mice model, the loss of immature DCs and the inability of mature splenic DCs to produce Th1 cytokines (i.e., IL-12) result in an immunosuppressive effect [65]. Additionally, in LPS-induced sepsis, endogenous glucocorticoids (immunosuppressive hormones) protect mice from LPS-induced septic shock by suppressing DC production of IL-12 (a cytokine required for IFN-γ production and lethality in LPS-induced septic shock) [65].…”
Section: The Role Of Dcs In Type 5 Crsmentioning
confidence: 99%
“…In a mice model, the loss of immature DCs and the inability of mature splenic DCs to produce Th1 cytokines (i.e., IL-12) result in an immunosuppressive effect [65]. Additionally, in LPS-induced sepsis, endogenous glucocorticoids (immunosuppressive hormones) protect mice from LPS-induced septic shock by suppressing DC production of IL-12 (a cytokine required for IFN-γ production and lethality in LPS-induced septic shock) [65]. Kobayashi et al[66] reported that B and T lymphocyte attenuator (CD272) inhibits LPS-induced endotoxic shock by suppressing TLR4 signaling and proinflammatory cytokine production in DCs.…”
Section: The Role Of Dcs In Type 5 Crsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological concentration of GCs can inhibit lymphocyte proliferation, differentiation and maturation, and synthesis, release and efficacy of cytokines in vivo and in vitro [12][13][14][15][16]. Physiological concentration of GCs enhances immunoglobulin production of human lymphocytes in vitro [17].…”
Section: Introductionmentioning
confidence: 99%